Distributed Applications and Interoperable Systems: 10th IFIP WG 6.1 International Conference, DAIS 2010, Amsterdam, The Netherlands, June 7-9, 2010, Proceedings - Eliassen, Frank; Kapitza, Rudiger (Lecture Notes in Computer Science, 2010)
Constitutes the refereed proceedings of the 10th IFIP WG 6.1 International Conference on Distributed Applications and Interoperable Systems, DAIS 2010, held in Amsterdam, The Netherlands, in June 2009.